Effect of Filler Size on the Thermal Properties of ER/BaTiO3 Composites. Issue 1 (30th October 2013) - Patsidis, Anastasios; Georga, Stavroula N.; Krontiras, Christoforos A.; Psarras, Georgios C.; Kanapitsas, Athanasios; Tsonos, Christos
Summary: Epoxy resin/barium titanate nano‐ and micro‐composites were prepared and studied, varying the filler content. Thermal properties of the composite systems were examined by means of Thermogravimetric/Differential Thermal Analysis, while dielectric response was assessed via Dielectric Relaxation Spectroscopy. Decomposition temperature found not to vary with filler size, while thermal stability of reinforced systems is enhanced compared to epoxy resin. Nanocomposites exhibit, improved thermal properties compared to micro‐composites at the same filler content. Composite systems attain higher values of dielectric permittivity, and relaxation processes are present in all studied systems.